The determinants and processes of SMEs’ internationalisation in the UK: a comparative analysis of SMEs in the East Midlands and London. - Whiteman, James (2022)
During the past four decades, internationalisation of SMEs within the UK has been rapidly increasing with the process of globalisation driving small and medium enterprises (SMEs) towards overseas expansion. Scholars studying this phenomenon have applied an array of concepts to explain SME internationalisation. However, the literature overlooks comparisons in UK based SMEs’ internationalisation processes and determinants. For purposes of this study, two sample firms were selected one of each from the East Midlands and London to examine contemporary SMEs progress against theorical frameworks and models. The comparative qualitative approach used by this study seeks to cross-analyse senior managers’ responses. Following an assessment of the responses, the findings point to three interconnected features influencing internationalisation: namely, the managerial, firm and environmental levels. The importance of these factors varied between the firms whereby London’s SME’s founder relied on experience as opposed to the East Midlands firm’s reliance on governmental assistance. Both firms, however, faced limitations during the initial start-up period. To overcome these limitations, networks were employed to provide a competitive advantage in their respective industries. Each firm was also exhibiting features aligned with internationalisation’s traditional and born global theories.